Estruturas comparativas complexas: variação e desvio e questões de tradução - Móia, Telmo; Marques, Rui (Revista da Associação Portuguesa de Linguística, 2019)
In this paper, we analyse two subtypes of related comparative constructions in Portuguese, with a focus on grammatical anomaly and change – whether expressed in translated text, as a result of calquing (from English), or in autochthonous text, evincing an area of grammatical instability and change in progress. These are: on the one hand, comparative clauses using multiplicative numbers or fractions, like the Portuguese counterparts of the president is twice as popular as the prime minister or women are four times less likely to develop coronary problems than men, and, on the other hand, nominal phrases resorting to the same quantifying operators, but in a non-clausal environment, like the counterparts of Spain has twice the level of unemployment of Portugal or this game console has four times the memory of the previous one. The observed anomalies – or disputed constructions – involve the non-canonical: (i) use of equative operators (tão/tanto, ‘as’) in comparative clauses with multiplicative numbers or fractions (likely, as a result of calquing from English); (ii) use of a connective (que/do que, ‘than’) in nominal phrases with quantifying operators similar to those of comparative clauses (likely, as a result of autochthonous hybridization); (iii) use of complex prepositional expressions like comparativamente com (‘in comparison with’) or em relação a (‘relatively to’) either instead of the connective (do) que in comparative clauses, or before modifiers inside nominal phrases with multiplicative numbers or fractions. Overall, an intriguing area of grammatical unrest is discussed, with a particular focus on its bearing on translating texts into standard Portuguese.